2016
DOI: 10.1111/echo.13323
|View full text |Cite
|
Sign up to set email alerts
|

Normal myocardial strain values using 2D speckle tracking echocardiography in healthy adults aged 20 to 72 years

Abstract: Our study resulted in normative LV GLS values assessed with QLAB 10. Male sex, higher BSA, and higher blood pressure negatively influence GLS. Therefore, these factors should be taken into account for strain interpretation in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 32 publications
8
67
1
Order By: Relevance
“…Previous cross‐sectional studies reported anthropometric and hemodynamic determinants of LS such as BMI, heart rate, and blood pressure . It was also shown that men have significantly lower LS compared to women even in healthy subjects without cardiovascular risk factors .…”
Section: Discussionmentioning
confidence: 97%
“…Previous cross‐sectional studies reported anthropometric and hemodynamic determinants of LS such as BMI, heart rate, and blood pressure . It was also shown that men have significantly lower LS compared to women even in healthy subjects without cardiovascular risk factors .…”
Section: Discussionmentioning
confidence: 97%
“…The effect of aging on GLS has remained controversial. Menting et al studied a healthy population 20–72 years old and found that GLS was reduced in individuals older than 55 years. Similar results were obtained by Sun et al and Dalen et al Conversely, analysis from the Framingham Heart Study, including healthy individuals 45–84 years old, did not find age‐associated changes in GLS .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that aging, 10 obesity, 11 and blood pressure (BP) 12 can reduce LV LS, but these findings have not been consistent across population studies. [10][11][12][13][14][15] Moreover, the available population studies were not controlled for physical fitness, and thus it remains unclear if LS is related to functional capacity in patients without HF.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy volunteers were enrolled in 2014–2015 for this prospective cross‐sectional study and stratified into 5 age groups: 20–29, 30–39, 40–49, 50–59, 60–72 years (n ≥ 28 for each group, each 50% female). Details have been published earlier . Briefly, subjects were recruited via advertisement and underwent a questionnaire regarding medical history and current health status, physical examination, venous blood sampling, 12‐lead ECG, and an echocardiogram.…”
Section: Methodsmentioning
confidence: 99%